Design of a Turbulence Generator of Medium Consistency Pulp Pumps - Hong Li; Haifei Zhuang; Weihao Geng (International Journal of Rotating Machinery)
The turbulence generator is a key component of medium consistency centrifugal pulp pumps, with functions to fluidize the medium consistency pulp and to separate gas from the liquid. Structure sizes of the generator affect the hydraulic performance. The radius and the blade laying angle are two important structural sizes of a turbulence generator. Starting with the research on the flow inside and shearing characteristics of the MC pulp, a simple mathematical model at the flow section of the shearing chamber is built, and the formula and procedure to calculate the radius of the turbulence generator are established. The blade laying angle is referenced from the turbine agitator which has the similar shape with the turbulence generator, and the CFD simulation is applied to study the different flow fields with different blade laying angles. Then the recommended blade laying angle of the turbulence generator is formed to be between 60° and 75°.